Tackling effectiveness in professional rugby league - Parmar, N. C.; James, N. (World Congress of Performance Analysis of Sport IX, 2012)
On average 300 tackles are made in a professional rugby league match with tackling proficiency suggested to be related to success (Gabbett et al., 2011). This study assessed tackling proficiency in terms of number of players committed, type of tackle, area of the pitch, tackle count and the outcome of the tackle. Ten London Broncos RLFC games (known as Harlequins Rugby League at the time) were randomly selected from the 2011 Engage Super League season with a balanced win loss record. Performance measures were defined specifically for this study and coded using the Focus X2 software (Elite Sports Analysis, 2002). Intra-observer reliability tests demonstrated <5% error for each of the variables examined. Data was analysed using the chi-square test for independence in the IBM SPSS Statistics package (v19, SPSS Inc, 2010). Results showed that the analysed team committed similar numbers of players into the tackle in both winning and losing matches but the success rate for tackling when just one man was committed was significantly lower (chi-square = 12.55, df = 1, p < 0.001, phi = 0.16) in losing matches (26.70%) compared to winning matches (42.20%). Similar success rates were shown between winning and losing matches when two (appr. 87%; chi-square = 0.35, df = 1, p = 0.55, phi = 0.02) or three or more players (appr. 96%; chi-square = 0.97, df = 1, p = 0.33, phi = 0.04) were committed. Further analysis revealed that it was when the opposition ran a C play (ball passed across the width of the pitch) that tackling success rate decreased from a success rate of 80.00% in winning matches to 53.40% in losing matches (chi-square = 21.99, df = 1, p < 0.001, phi = 0.28). This tackling success rate was also different between winning and losing matches when the opposition ran the A/B play (81.40% and 76.90% respectively; chi-square = 4.19, df = 1, p < 0.05, phi = 0.05) but there was no difference for the scoot play (appr. 73% success rate; chi-square = 0.01, df = 1, p = 0.93, phi = 0.01). This analysis has showed where this particular team performed at a lower level during losing matches. This was shown to be a lower success rate of tackling when only one man was committed to the tackle and this seemed to be more prevalent when the opposition ran a C play. It is suggested that the use of the effect size (phi) in this study gives better practical information for coaches than the significance level. For example tackling success rate for the A/B plays was significantly different (p < 0.05) but the effect size (0.05) was very small suggesting that there was no general difference in performance although just one missed tackle at a crucial point in time could be the difference between winning and losing! Future studies could further this research by adding more performance variables and compare between different levels of playing standard.